New Species of Diaporthales (Ascomycota) from Diseased Leaves in Fujian Province, China - Xiayu Guan; Taichang Mu; Nemat O. Keyhani; Junya Shang; Yuchen Mao; Jiao Yang; Minhai Zheng; Lixia Yang; Huili Pu; Yongsheng Lin; Mengjia Zhu; Huajun Lv; et al. (Journal of Fungi)
Fungal biota represents important constituents of phyllosphere microorganisms. It is taxonomically highly diverse and influences plant physiology, metabolism and health. Members of the order Diaporthales are distributed worldwide and include devastating plant pathogens as well as endophytes and saprophytes. However, many phyllosphere Diaporthales species remain uncharacterized, with studies examining their diversity needed. Here, we report on the identification of several diaporthalean taxa samples collected from diseased leaves of Cinnamomum camphora (Lauraceae), Castanopsis fordii (Fagaceae) and Schima superba (Theaceae) in Fujian province, China. Based on morphological features coupled to multigene phylogenetic analyses of the internal transcribed spacer (ITS) region, the large subunit of nuclear ribosomal RNA (LSU), the partial beta-tubulin (tub2), histone H3 (his3), DNA-directed RNA polymerase II subunit (rpb2), translation elongation factor 1-α (tef1) and calmodulin (cal) genes, three new species of Diaporthales are introduced, namely, Diaporthe wuyishanensis, Gnomoniopsis wuyishanensis and Paratubakia schimae. This study contributes to our understanding on the biodiversity of diaporthalean fungi that are inhabitants of the phyllosphere of trees native to Asia.